2013
DOI: 10.1021/jp4041315
|View full text |Cite
|
Sign up to set email alerts
|

Base-Specific Ionization of Deprotonated Nucleotides by Resonance Enhanced Two-Photon Detachment

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 65 publications
(147 reference statements)
5
36
0
1
Order By: Relevance
“…The k 1 high energy cutoff of 3.1 eV agrees well with the adiabatic detachment energy for the nucleobase within dGMP -, which was found to be 4.65 eV. 28 The negative intensity of k 1 < 1 eV is indicative of a population transfer from the higher eKE region to the lower eKE region. Note that the extracted τ 1 lifetime is within our temporal resolution.…”
Section: Dgmp -supporting
confidence: 68%
See 2 more Smart Citations
“…The k 1 high energy cutoff of 3.1 eV agrees well with the adiabatic detachment energy for the nucleobase within dGMP -, which was found to be 4.65 eV. 28 The negative intensity of k 1 < 1 eV is indicative of a population transfer from the higher eKE region to the lower eKE region. Note that the extracted τ 1 lifetime is within our temporal resolution.…”
Section: Dgmp -supporting
confidence: 68%
“…A key feature of this experimental scheme is that, although in principle the total photon energy (7.76 eV) is sufficient to detach the electron from many parts of the anion, including the charge carrying phosphate group, by exploiting the 1 ππ* ← S 0 resonance, we can selectively detach electrons only from the nucleobase moiety. 28 This allows us to think of the experiment as photoelectron spectroscopy on a neutral subgroup, whilst the charged phosphate group remains a spectator. In our previous dAMP -experiments, we found that the excited state dynamics of the nucleotide could be modelled using biexponential kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their experiment, Yang et al  [117] were able to one-photon ionize from the sugar and the phosphate as well as the base, whereas Chatterley et al could only resonantly two-photon ionize the base. As such, in the work by Yang et al , the lowest electron binding energy in dAMP − , dTMP − and dCMP − was attributed to photodetachment from the phosphate moiety, whereas for dGMP − , the lowest binding energy site corresponds to photodetachment from the base moiety, in agreement with Chatterley et al  [109].
Figure 11.( a ) Two-photon resonant photodetachment spectra of (top–bottom) dAMP − , dTMP − , dCMP − and dGMP − , ( b ) time-resolved total electron yield of dGMP − fit to two exponential decays yielding lifetimes of less than 50 fs (red) and approximately 700 fs (blue) and ( c ) time-resolved photoelectron spectrum of dGMP − .
…”
Section: Excited-state Dynamics: the Current State Of The Artsupporting
confidence: 71%
“…Chatterley et al  [109] have performed experiments on the deprotonated nucleotide anions of all four DNA bases by coupling ESI with TR-PES using an experimental set-up described in detail separately [116]. In this work, dXMP − (where X is a DNA base, for example, dGMP − would be 2′deoxy-guanosine 5′-monophosphate, see figure 1 b ) was generated via ESI from an approximately 0.5 mM solution of either dXMP or its sodium salt in methanol.…”
Section: Excited-state Dynamics: the Current State Of The Artmentioning
confidence: 99%